THE SPEECH STYLES USED BY ERIN GRUWELL IN FREEDOM WRITERS MOVIE - Elma Ariella Setiawan; Esther H Kuntjara (Institute of Research and Community Outreach - Petra Christian University, 2017)
This study focused on the gendered speech styles namely; male speech styles and female speech styles used by Erin Gruwell in the Freedom Writers movie and the changes that can be perceived from her use of gendered speech styles. Based on the writer’s descriptive qualitative approach analysis on the data, she found out that the teacher uses both male speech styles and female speech styles along 15 class scenes. She used Co-operative feature of female speech styles and Aggressive feature of male speech styles as her dominant feature which were used in each class scene. However, the writer could not find any gradual changes from the teacher’s use of speech styles. Therefore, the teacher’s changes in using speech styles did not seem to correlate with the students’ changes in the attitude towards the teacher.